Electrochemical device and electrical equipment including same
Patent Information
- Application Number
- JP2024547856
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-31
- Filing Date
- 2023-01-09
- Publication Date
- 2025-03-05
Smart Images

Figure 2025506053000001 
Figure 2025506053000002 
Figure 2025506053000003
Abstract
Description
CROSS REFERENCE TO CORRESPONDING APPLICATIONS
[0001] The present invention is based on and claims priority to a Chinese patent application having application number 202210335359.9, filing date March 31, 2022, and title "Electrochemical Apparatus and Electrical Apparatus Including the Same," the entire contents of which are incorporated herein by reference. [Technical field]
[0002] The present invention relates to the technical field of energy storage, and more particularly to electrochemical devices and electrical appliances containing same. [Background technology]
[0003] At present, the concepts of carbon neutrality and carbon peak-out have accelerated and promoted the development of the new energy industry. Lithium batteries are an important part of the new energy industry. As the demand for lithium batteries expands, the demand for transition metal elements such as cobalt, nickel, and manganese as raw materials is also constantly increasing, which has led to an increase in the prices of related resources such as cobalt and nickel. Therefore, in this field, it is necessary to reduce costs by increasing the content of manganese (Mn) in the positive electrode material. However, if the content of manganese element in the positive electrode active material is high, it is easy to cause the problem of leaching, and the leached manganese will accumulate on the negative electrode, causing the destruction of the negative electrode interface protective film layer (SEI (solid electrolyte interphase)), resulting in poor cycle performance and storage performance of the lithium battery. Summary of the Invention
[0004] The present invention has been made in consideration of the problems existing in the above-mentioned conventional art, and aims to provide an electrochemical device and an electrical device including the same, which solves the above-mentioned problem of eliminating or at least reducing the problem of reduced cycle performance and storage performance of lithium batteries that occurs when a high manganese content is used in the positive electrode active material.
[0005] In order to achieve the above object, the present invention provides an electrochemical device and an electrical appliance including the same.
[0006] In one aspect, the present invention provides an electrochemical device comprising a positive electrode, a negative electrode, a separator, and an electrolyte, the electrolytic solution contains fluoroethylene carbonate, and the content a of the fluoroethylene carbonate is 0.01% to 5% based on the mass of the electrolytic solution; the positive electrode includes a positive electrode active material, the positive electrode active material includes a Mn element, and the content of the Mn element is 15% or more with respect to the mass of the positive electrode active material; The unit reaction area of the positive electrode active material is cm 2 / cm 2 In this case, a and c satisfy 0.0006≦a / c≦6.25, and the unit reaction area is a unit area (cm 2 ) and the specific surface area BET (m 2 / g).
[0007] In any embodiment, the electrochemical device comprises: a and c satisfy 0.0006≦a / c≦2.5; The content of the fluoroethylene carbonate is 0.05% to 5% based on the mass of the electrolyte; W is 8mg / cm 2 ~35mg / cm 2 The range is 1m 2 / g~5m 2 / g.
[0008] In any embodiment, when Dv10 / Dv99 of the positive electrode active material is z, a / z is 0.01 to 1.
[0009] In any embodiment, the electrolyte further contains vinylene carbonate (VC), and the content b of the vinylene carbonate is 0.01% to 5% based on the mass of the electrolyte.
[0010] In any embodiment, b and a satisfy 0.11a - 0.05% < b < 5.1a + 0.45%.
[0011] In any embodiment, in the positive electrode active material, when the content of the Mn element is x, b and x satisfy b / x ≥ 10 -3 and satisfy.
[0012] In any embodiment, the electrolyte further contains additive A, and the additive A is at least one selected from the group consisting of methylene methanedisulfonate (MMDS), 1,3 - propenesultone (PES), 1,3 - propane sultone (PS), succinic anhydride (SA), lithium difluorophosphate (LiPO 2 F 2 )), 2 - fluoropyridine (2 - PY), and lithium bis(fluorosulfonyl)imide (LiFSI).
[0013] In any embodiment, the content of the additive A is 0.01% to 10% based on the mass of the electrolyte.
[0014] In any embodiment, the electrolyte further contains dimethyl carbonate (DMC), and the content of the dimethyl carbonate is 5% or less based on the mass of the electrolyte.
[0015] In any embodiment, the positive electrode active material contains at least one of lithium manganate and lithium nickel cobalt manganate.
[0016] In any embodiment, the electrochemical device the content of the fluoroethylene carbonate is 0.05% to 3% based on the mass of the electrolyte, and W is 13 mg / cm2 ~30mg / cm 2 The range is 1.2m 2 / g~3.5m 2 / g range, The electrolytic solution further contains vinylene carbonate (VC), and the content of the vinylene carbonate is 0.01% to 2% based on the mass of the electrolytic solution; The electrolytic solution further contains dimethyl carbonate, and the content of the dimethyl carbonate is 1% or less based on the mass of the electrolytic solution; In the positive electrode active material, the content of Mn element is 60% or less; When Dv10 / Dv99 of the positive electrode active material is z, a / z is 0.05 to 0.3.
[0017] Meanwhile, the present invention further provides an electrical appliance including the above-mentioned electrochemical device.
[0018] The inventor unexpectedly found that when the manganese content in the positive electrode active material is increased, the ratio of the fluoroethylene carbonate content in the electrolyte and the unit reaction area of the positive electrode active material can be controlled within the range of the present invention, which can significantly improve the cycle performance and storage performance of the battery, thereby ensuring the performance requirements of the battery after increasing the manganese content in the positive electrode material, and thereby achieving both the cost and performance of the battery product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, the electrochemical device and the manufacturing method thereof, the positive electrode piece, the negative electrode piece, the electrolyte, and the electric device of the present invention will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of already known matters and duplicated description of the same configuration may be omitted. This is to avoid unnecessary redundancy of the following description and to allow those skilled in the art to easily understand. Furthermore, the following description is provided to allow those skilled in the art to fully understand the present invention, and is not intended to limit the subject matter described in the claims.
[0020] It should be noted that quantities, ratios, and other numerical values may be expressed herein in a range format. It should be understood that such range format is used for convenience and brevity, and should be understood to include not only the numerical values explicitly specified as range limits, but also all individual numerical values or subranges contained within the range, such that each numerical value and subrange is explicitly specified.
[0021] The "ranges" disclosed in the present invention are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of a particular range. The ranges defined in this way may be inclusive or exclusive of the end values, and may be arbitrarily combinable, i.e., any lower limit may be combined with any upper limit to form a range.
[0022] All and any embodiments of the present invention can be combined with each other to form a new technical solution, unless otherwise specified.
[0023] All technical features and optional technical features of the present invention can be combined with each other to form a new technical solution, unless otherwise specified.
[0024] Unless otherwise specified, the terms "comprise" and "contain" referred to in the present invention may be open-ended or closed-ended. For example, the terms "comprise" and "contain" may mean that other components not listed are also included or contained, or that only the listed components are included or contained.
[0025] As used herein, the terms "more than" and "less than" are inclusive of number, for example, "one or more" means one or more, and "one or more of A and B" means "A", "B", or "A and B".
[0026] As used herein, the term "at least one" means one or more, for example, "at least one of A, B, and C" means "A," "B," "C," "A and B," "A and C," "B and C," or "A, B, and C."
[0027] In the present invention, the term "or" is inclusive unless otherwise specified. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, any of the following conditions satisfy the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); and both A and B are true (or exist).
[0028] Fluoroethylene carbonate is also known as 4-Fluoro-1,3-dioxolan-2-one.
[0029] Unless otherwise specified, all contents and percentages in the present specification are by weight.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0031] A high content of manganese in the positive electrode active material is prone to leaching problems, and the leached manganese will accumulate on the negative electrode, leading to the destruction of the negative electrode interface protective layer (SEI), and further reducing the cycle performance and storage performance of the lithium battery. After a large amount of experiments, the present inventors have found that the use of the electrochemical device of the present invention can significantly improve the above problems.
[0032] Accordingly, a first aspect of the present invention is an electrochemical device comprising a positive electrode, a negative electrode, a separator and an electrolyte, the electrolytic solution contains fluoroethylene carbonate, and the content a of the fluoroethylene carbonate is 0.01% to 5% based on the mass of the electrolytic solution; the positive electrode includes a positive electrode active material, the positive electrode active material includes a Mn element, and a content x of the Mn element is 15% or more with respect to a mass of the positive electrode active material, The unit reaction area of the positive electrode active material is cm 2 / cm 2 where a and c satisfy 0.0006≦a / c≦6.25, and the unit reaction area is the product of the weight W of the positive electrode active material per unit area and the specific surface area BET of the positive electrode active material.
[0033] In some embodiments, the Mn element content x is 25% or more, based on the mass of the positive electrode active material. In some embodiments, the Mn element content x is 30% or more, based on the mass of the positive electrode active material. In some embodiments, the Mn element content x is 60% or less, based on the mass of the positive electrode active material.
[0034] Regardless of any theory, the present inventor believes that fluoroethylene carbonate (FEC) oxidizes and decomposes on the surface of the positive electrode, and together with the lithium salt in the electrolyte, forms a protective layer on the surface of the positive electrode, which can reduce manganese elution, and at the same time forms a stable protective layer on the negative electrode, which can reduce the destruction caused by the reduction of manganese eluted from the positive electrode at the negative electrode. However, FEC itself has poor thermal stability and can decompose to generate HF, which in turn promotes the elution of manganese into the positive electrode. As a result of research, the present inventor has found that when a high content of manganese is used in the positive electrode active material, by controlling the ratio of the FEC content (a, relative to the mass of the electrolyte) to the unit reaction area of the positive electrode active material (c, the product of the weight W of the positive electrode active material per unit area and the specific surface area BET of the positive electrode active material) within the range of the present invention, the protective effect of FEC against the film formation of the positive and negative electrodes can be sufficiently ensured, and at the same time, the adverse effects of high content decomposition can be reduced.
[0035] electrolyte The electrolyte serves as an ionic conductor between the positive and negative electrode pieces and includes an electrolyte lithium salt and a solvent.
[0036] In some embodiments, the electrolyte lithium salt may be at least one selected from the group consisting of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, lithium fluoroaluminate, lithium tetrachloroaluminate, lithium chloride, lithium fluoride, lithium perfluorobutanesulfonate, and lithium tetrafluoro(oxalato)phosphate.
[0037] In some embodiments, the content of the electrolyte lithium salt may be 1% by mass to 30% by mass relative to the mass of the electrolyte solution. In some embodiments, the content of the electrolyte lithium salt is 5% by mass to 20% by mass relative to the mass of the electrolyte solution. In some embodiments, the content of the electrolyte lithium salt is 8% by mass to 15% by mass relative to the mass of the electrolyte solution.
[0038] In some embodiments, the solvent may be at least one selected from the group consisting of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dioxolane, dimethyl ether, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0039] In some embodiments, the content of the solvent may be 20% by weight or more, based on the weight of the electrolyte. In some embodiments, the content of the solvent may be 30% by weight or more, based on the weight of the electrolyte. In some embodiments, the content of the solvent may be 40% by weight or more, based on the weight of the electrolyte. In some embodiments, the content of the solvent may be 50% by weight or more, based on the weight of the electrolyte. In some embodiments, the content of the solvent may be 60% by weight or more, based on the weight of the electrolyte.
[0040] In some embodiments, the electrolyte contains fluoroethylene carbonate, and the content a of the fluoroethylene carbonate is 0.01% to 5%. In some embodiments, the content a of the fluoroethylene carbonate is 0.05% to 3% based on the mass of the electrolyte. In some embodiments, the content a of the fluoroethylene carbonate is 0.05% to 2% based on the mass of the electrolyte.
[0041] In some embodiments, the electrolyte further contains vinylene carbonate (VC), and the content b of the vinylene carbonate is 0.01% to 5%. In some embodiments, the content b of the vinylene carbonate is 0.01% to 4% based on the mass of the electrolyte. In some embodiments, the content b of the vinylene carbonate is 0.01% to 2% based on the mass of the electrolyte.
[0042] In some embodiments, b and a satisfy 0.11a - 0.05% < b < 5.1a + 0.45%.
[0043] In some embodiments, the electrolyte further contains additive A, and the additive A is at least one selected from the group consisting of methylene methanedisulfonate (MMDS), 1,3 - propenesultone (PES), 1,3 - propane sultone (PS), succinic anhydride (SA), lithium difluorophosphate (LiPO 2 F 2 )), 2 - fluoropyridine (2 - PY), and lithium bis(fluorosulfonyl)imide (LiFSI).
[0044] In some embodiments, the additive A is at least one selected from the group consisting of 1,3 - propane sultone and 2 - fluoropyridine.
[0045] In some embodiments, the content of the additive A is 0.01% to 10% by mass of the electrolytic solution. In some embodiments, the content of the additive A is 0.01% to 6% by mass of the electrolytic solution.
[0046] In some embodiments, the electrolyte further comprises dimethyl carbonate (DMC), and the content of the dimethyl carbonate is 5% or less based on the mass of the electrolyte.
[0047] In some embodiments, the content of the dimethyl carbonate is 1% or less by mass of the electrolyte solution.
[0048] In some embodiments, the electrolyte further includes other additives. For example, the additives may include a negative electrode film-forming additive, a positive electrode film-forming additive, and may also include additives that can improve certain performance of the battery, such as an additive that improves the overcharge performance of the battery, or an additive that improves the high temperature or low temperature performance of the battery.
[0049] positive electrode In the present invention, the positive electrode is a positive electrode piece including a positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector.
[0050] As an example, the positive electrode current collector has two surfaces opposing each other in the thickness direction of the positive electrode current collector, and a positive electrode film layer is provided on one or both of the two opposing surfaces of the positive electrode current collector.
[0051] The positive electrode film layer includes a positive electrode active material, the positive electrode active material includes Mn element, the content x of the Mn element is 15% to 60% with respect to the mass of the positive electrode active material, and the unit reaction area of the positive electrode active material is cm 2 / cm 2where a and c satisfy 0.0006≦a / c≦6.25, where the unit reaction area is the product of the weight W of the positive electrode active material per unit area and the specific surface area BET of the positive electrode active material. In some embodiments, a and c satisfy 0.001≦a / c≦4.5. In some embodiments, a and c satisfy 0.001≦a / c≦2.5.
[0052] In some embodiments, W is 8 mg / cm 2 ~35mg / cm 2 The range is 1m 2 / g~5m 2 In some embodiments, W is in the range of 13 mg / cm 2 ~30mg / cm 2 The range is 1.2m. 2 / g~3.5m 2 / g range.
[0053] In some embodiments, b and x are such that b / x≧10. -3 where b is the content of vinylene carbonate and x is the content of Mn element. In some embodiments, b and x satisfy b / x≦0.1.
[0054] In some embodiments, x and a are x×e a is 0.1 to 1.2, where e is the base of the natural logarithm. In some embodiments, x×e a The value is 0.15 to 0.7.
[0055] In the present invention, the specific surface area BET is measured by nitrogen adsorption method (GB / T 19587-2017). For example, before the measurement, the sample is baked in a vacuum oven at 120°C for 2 hours, and then the 6-point BET method (i.e., P / P0=0.05 / 0.10 / 0.15 / 0.2 / 0.25 / 0.3) is used for the measurement. The purity of the nitrogen gas used is 99.999%, and the temperature of liquid nitrogen is -196°C.
[0056] The weight W of the positive electrode active material layer per unit area is measured by the following method: a positive electrode piece having a certain area S and having a positive electrode active material layer on two surfaces of a current collector is taken, the positive electrode active material layer is scraped off from the positive electrode current collector (scraping off materials other than the current collector), and the weight m of the powder is weighed, and the weight W per unit area is calculated by W = m / (S x 2). A positive electrode having a certain area S1 and an active material layer on one surface of a current collector is taken, the positive electrode active material layer is scraped off from the positive electrode current collector (scraping off materials other than the current collector), and the weight m1 of the powder is weighed, and the weight per unit area W is calculated by W=m1 / S1.
[0057] The weight W (g / cm) of the positive electrode active material layer per unit area 2 ) and the specific surface area BET(m 2 / g) to obtain the unit reaction area c (m 2 / cm 2 ) is obtained.
[0058] In some embodiments, the positive electrode active material may further include at least one of a lithium-containing phosphate having an olivine structure, a lithium transition metal oxide, and a modified compound of each of them. However, the present invention is not limited to these materials, and other conventional materials used as positive electrode active materials in batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Here, examples of lithium transition metal oxides include lithium cobalt oxide (e.g., LiCoO 2 ), lithium nickel oxide (e.g. LiNiO 2 ), lithium manganese oxide (e.g. LiMnO 2 , LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g. LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2(which can also be abbreviated as NCM333), lithium nickel cobalt aluminum oxide (e.g. LiNi 0.85 Co 0.15 Al 0.05 O 2 ) and modified compounds thereof. Examples of lithium-containing phosphates having an olivine structure include, but are not limited to, lithium iron phosphate (e.g., LiFePO 4 (which can also be abbreviated as LFP), lithium iron phosphate and carbon composites, lithium manganese phosphate (e.g., LiMnPO 4 ), a composite of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite of lithium iron manganese phosphate and carbon.
[0059] In some embodiments, the content of the positive electrode active material in the positive electrode membrane layer is 80 wt % or more, and optionally 90 wt % or more, based on the total weight of the positive electrode membrane layer. In some embodiments, the content of the positive electrode active material in the positive electrode membrane layer is 95 wt % or more, based on the total weight of the positive electrode membrane layer.
[0060] In some embodiments, when the Dv99 of the positive electrode active material is y μm, y is in the range of 20 to 60. In some embodiments, y is in the range of 25 to 55. In some embodiments, y is in the range of 30 to 53.
[0061] In the present invention, if the particles of the positive electrode active material are too small, the reaction contact area is large and many side reactions occur, but if the particles of the positive electrode active material are too large, the ion transport path inside the particles becomes long, affecting performance.
[0062] In the present invention, the Dv10 and Dv99 of the positive electrode active material can be measured by using a laser particle size analyzer (e.g., Malvern Master Size 3000) with reference to GB / T 19077.1-2016. Here, the physical definitions of Dv10 and Dv99 are as follows. Dv10: The particle size corresponding to when the cumulative volume distribution rate of the positive electrode active material reaches 10%. Dv99: The particle size corresponding to when the cumulative volume distribution rate of the positive electrode active material reaches 99%.
[0063] In some embodiments, y and a satisfy that the value of (π × y 2 ) / (10000 × a) is 0.01 to 115. In some embodiments, the value of (π × y 2 ) / (10000 × a) is 0.01 to 20. In some embodiments, the value of (π × y 2 ) / (10000 × a) is 0.01 to 10.
[0064] In some embodiments, the Dv10 of the positive electrode active material is 3 μm to 10 μm. In some embodiments, the Dv10 of the positive electrode active material is 3.2 μm to 8 μm.
[0065] In some embodiments, when z is defined as Dv10 / Dv99 of the positive electrode active material, z is in the range of 0.01 to 0.5, and the value of a / z is 0.01 to 1. In some embodiments, z is in the range of 0.05 to 0.4. In some embodiments, the value of a / z is 0.05 to 0.3.
[0066] In some embodiments, the positive electrode active material contains lithium manganate LiMn 2 O 4 and optionally contains lithium nickel cobalt manganate Li x Ni m Co n Mn p O 2 where 0.95 ≦ x ≦ 1.05, 0.98 ≦ m + n + p ≦ 1.02, and 0 ≦ m < 1, 0 ≦ n < 1, 0 < p ≦ 1 (for example, LiNi 0.8 Co 0.1 Mn 0.1 O 2 ), and optionally contains LiFeO 4 .
[0067] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, an aluminum foil may be used as the metal foil. The composite current collector may include a polymeric substrate layer and a metal layer formed on at least one surface of the polymeric substrate layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy) on a polymeric substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene, polyethylene (PE)).
[0068] In some embodiments, the positive electrode membrane layer further includes a binder. For example, the binder can include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0069] In some embodiments, the content of the binder in the positive electrode membrane layer may be 0.1 wt % to 6 wt %, optionally 0.5 wt % to 5 wt %, and more preferably 0.8 wt % to 3 wt %, based on the total weight of the positive electrode membrane layer.
[0070] In some embodiments, the positive electrode membrane layer further includes a conductive agent. For example, the conductive agent can include at least one of superconducting carbon, acetylene black, carbon black, carbon nanotubes, graphene, and carbon nanofibers.
[0071] In some embodiments, the content of the conductive agent in the positive electrode membrane layer may be 0.1% to 6% by weight, optionally 0.5 to 5% by weight, and more preferably 0.8 to 3% by weight, based on the total weight of the positive electrode membrane layer.
[0072] In some embodiments, the positive electrode pieces can be manufactured as follows: The components for manufacturing the positive electrode pieces, such as the positive electrode active material, the conductive agent, the binder, and other optional components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, and the positive electrode slurry is applied to a positive electrode current collector, and the positive electrode pieces can be obtained through processes such as drying and cold rolling.
[0073] negative electrode In the present invention, the negative electrode is a negative electrode piece, which includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, and the negative electrode film layer includes a negative electrode active material.
[0074] As an example, the negative electrode current collector has two surfaces opposing each other in the thickness direction of the negative electrode current collector, and the negative electrode film layer is provided on either one or both of the two opposing surfaces of the negative electrode current collector.
[0075] In some embodiments, the negative electrode current collector can be a metal foil or a composite current collector. For example, the metal foil can be a copper foil. The composite current collector can include a polymeric substrate layer and a metal layer formed on at least one surface of the polymeric substrate layer. The composite current collector can be formed by forming a metal material (such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy) on a polymeric substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene, polyethylene (PE)).
[0076] In some embodiments, the negative electrode active material may be a negative electrode active material for batteries known in the art. As an example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based material, tin-based material, lithium titanate, and the like. The silicon-based material may be at least one selected from the group consisting of elemental silicon, silicon-oxygen compound, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy. The tin-based material may be at least one selected from the group consisting of elemental tin, tin-oxygen compound, and tin alloy. However, the present invention is not limited to these materials, and other conventional materials used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0077] In some embodiments, the weight fraction of the negative electrode active material in the negative electrode membrane layer is 80% or more, optionally 90% or more, more preferably 95% or more. In some embodiments, the negative electrode membrane layer optionally further comprises a binder. As an example, the binder may be at least one selected from the group consisting of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0078] In some embodiments, the weight fraction of the binder in the negative electrode membrane layer may be 0.1% to 6% by weight, optionally 0.5 to 5% by weight.
[0079] In some embodiments, the negative electrode membrane layer further includes an optional conductive agent. For example, the conductive agent may be at least one selected from the group consisting of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0080] In some embodiments, the weight fraction of the conductive agent in the negative electrode membrane layer may be 0.1% to 6% by weight, optionally 0.5 to 5% by weight.
[0081] In some embodiments, the negative electrode membrane layer optionally includes other auxiliary agents, such as a thickening agent (eg, carboxymethyl cellulose (CMC)).
[0082] In some embodiments, the negative electrode pieces can be manufactured as follows: The above-mentioned components for manufacturing the negative electrode pieces, such as the negative electrode active material, the conductive agent, the binder, and other optional components, are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, and the negative electrode slurry is applied to a negative electrode current collector, and the negative electrode pieces can be obtained through processes such as drying and cold rolling.
[0083] Separator In the present invention, the type of separator is not particularly limited, and any known separator having good chemical stability and mechanical stability can be selected. The material of the separator may be at least one selected from the group consisting of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film, and is not particularly limited. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, and is not particularly limited.
[0084] In the present invention, the positive electrode pieces, the negative electrode pieces, and the separator can be fabricated into an electrode assembly by a winding process or a stacking process.
[0085] In the present invention, the lithium metal battery can include a housing, which can be used to enclose the electrode assembly and electrolyte described above.
[0086] In the present invention, the exterior of the lithium metal battery may be a hard case such as a hard plastic case, an aluminum case, or a steel case. The exterior of the lithium metal battery may be a soft pack such as a pouch-shaped soft pack. The material of the soft pack may be plastic. Examples of plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0087] In the present invention, the shape of the lithium metal battery is not particularly limited, and may be cylindrical, rectangular, or other shapes.
[0088] Another aspect of the present invention provides an electrical appliance comprising an electrochemical device as described above. Working Example
[0089] Hereinafter, the embodiments of the present invention will be described by specific specific examples. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied by different specific embodiments. Each detail of the specification can be modified or changed in various ways without departing from the spirit of the present invention based on different viewpoints and applications.
[0090] The preparation process of the lithium-ion battery is as follows: (1) Preparation of positive electrode pieces The positive electrode active material (single positive electrode material or mixed positive electrode material), Super P as a conductive agent, and polyvinylidene fluoride as a binder were mixed in a weight ratio of 97:1.4:1.6, N-methylpyrrolidone (NMP) was added, and the mixture was uniformly stirred by a vacuum mixer to obtain a positive electrode slurry. Here, the solid content of the positive electrode slurry was 72% by weight. The positive electrode slurry was uniformly applied onto aluminum foil as a positive electrode current collector, and the applied aluminum foil was dried at 100°C, and then cold-rolled, punched, and divided to obtain a positive electrode piece with a specification of 74 mm x 867 mm, and a tab was welded for later use.
[0091] (2) Preparation of negative electrode pieces Artificial graphite as the negative electrode active material, Super P as the conductive agent, sodium carboxymethylcellulose (CMC-Na) as the thickener, and styrene butadiene rubber (SBR) as the binder were mixed in a weight ratio of 96:2:0.8:1.2, deionized water was added, and the mixture was uniformly stirred by a vacuum mixer to obtain a negative electrode slurry. Here, the solid content of the negative electrode slurry was 54% by weight. The negative electrode slurry was uniformly applied onto copper foil as a negative electrode current collector, and the applied copper foil was dried at 85°C, and then cold-rolled, punched, and divided to obtain a negative electrode piece with a specification of 79 mm x 872 mm, and a tab was welded for later use.
[0092] (3) Preparation of electrolyte In a glove box with a dry argon gas atmosphere, the solvents were mixed in a ratio of ethylene carbonate (EC):diethyl carbonate (DEC):methyl ethyl carbonate (EMC) = 3:5:2 (mass ratio), and then lithium hexafluorophosphate (12.5 wt%, based on the mass of the basic electrolyte) was added to obtain a basic electrolyte. The appropriate additives were added to the basic electrolyte according to the type and mass content listed in the table below, dissolved, thoroughly stirred and mixed uniformly, and then an electrolyte was obtained. The content of the additives listed in each table was based on the mass of the electrolyte.
[0093] (4) Preparation of separator A polyethylene (PE) substrate layer with a thickness of 9 μm was selected, and polyvinylidene fluoride (PVDF) slurry, inorganic particles (flake boehmite and Al 2 O 3 The slurry (ratio of 70:30) was applied to one side of a polyethylene substrate layer and dried to obtain the final separator, where the coating thickness was 3 μm and the porosity of the separator was 55%.
[0094] (5) Preparation of lithium-ion batteries The positive electrode pieces, separator, and negative electrode pieces were stacked in order so that the separator was interposed between the positive electrode pieces and the negative electrode pieces to function as a separator, and then wound up to obtain an electrode assembly. After welding the tabs, the electrode assembly was placed in an exterior aluminum plastic film foil, and the electrolyte prepared above was injected into the dried electrode assembly, which was then vacuum sealed, left to stand, formed (charged at a constant current of 0.02C to 3.3V, then charged at a constant current of 0.1C to 3.6V), shaped, and measured the capacity (charged at a constant current and voltage of 0.5C to 4.2V, then discharged at 0.5C to 3.0V), to obtain a soft-pack lithium-ion battery.
[0095] It is necessary to explain here that in the following Example 1-1, the positive electrode active material is LiMn 2 O 4 Particles and 10% LiNi by mass content 0.8 Co 0.1 Mn 0.1 O 2 The positive electrode active material had a Dv99 of 45 μm and a Dv10 of 10 μm.
[0096] Unless otherwise noted, in Table 1, the batteries of Example 1-1 and other Examples are manufactured in substantially the same manner, and the only difference between them was adjusting the content of FEC and the related parameters of the positive electrode active material described in Table 1. Similarly, in Table 2, the manufacturing method of the batteries of Examples 2-1 to 2-10 is substantially the same as that of Example 1-4, and the only difference between them was using FEC with different contents and positive electrode active materials with different types and particle sizes. Here, it can be understood that materials with different Dv99 and Dv10 can be obtained by adjusting the sintering temperature and time in the preparation process, and the content of Mn element can be fine-tuned by element doping as necessary. In Table 3, the manufacturing method of the batteries of Examples 3-1 to 3-8 is substantially the same as that of Example 1-4, and the only difference between them was using FEC with different contents and adding vinylene carbonate with different contents. In Table 4, the manufacturing method of the batteries of Examples 4-1 to 4-15 is substantially the same as that of Example 1-4, and the only difference between them was using additives with different types and contents. In Table 5, the manufacturing methods of the batteries of Examples 5-1 to 5-4 were substantially the same as those of Example 1-4, with the only difference being that different amounts of dimethyl carbonate were used.
[0097] Measuring performance Cycle measurements and cycle thickness changes The battery core is placed in a high temperature box at 45°C, and charged at a constant current and constant voltage of 0.5C up to 4.2V. The measured thickness is h 1 The battery was discharged at a constant current of 0.5 C to 3.0 V, and then left to stand for 15 minutes. This constituted one cycle. The capacity at the first cycle was C 1 After 100 cycles, the discharge capacity at the 100th cycle was measured as C 100 Let the thickness be h 100 The cycle capacity retention rate is [C 100 / C 1 ] × 100%, and the thickness change rate is [(h 100 / h 1 )-1] × 100%.
[0098] Low temperature discharge measurement The battery core is placed in a high and low temperature box and the temperature is adjusted to 25°C. Then, it is charged at a constant current and constant voltage of 0.2C to 4.2V, and then discharged at 0.2C to 3.0V. The discharge capacity at this time is C 25 The battery was charged at a constant current and constant voltage of 0.2C up to 4.2V, and then the temperature of the high and low temperature box was adjusted to -20°C. The battery was discharged at a constant current of 0.2C up to 3.0V. The discharge capacity at this time was C -20 (mAh). The low-temperature discharge capacity retention rate is [C -20 / C 25 ]×100%.
[0099] High temperature fully charged storage First, the battery core was charged at a constant current and constant voltage of 0.5C at 25°C up to 4.35V, and then discharged at 0.2C down to 3.0V (discharge capacity is C 0 Then, the film was charged at a constant current and constant voltage of 0.5 C up to 4.35 V, and the initial thickness d 1 After that, the battery core was placed in a high-temperature furnace at 60°C and stored for 30 days, after which the thickness d 2 After the storage was completed, the battery core was discharged at 0.2C at 25°C to 3.0V, then charged at a constant current and constant voltage of 0.5C to 4.35V, and then discharged at 0.2C to 3.0V (discharge capacity was C 30 (Assuming that.) The thickness change rate during high-temperature storage at full charge is [(d 2 / d 1 )-1] × 100%. The recoverable capacity after storage at 60°C for 30 days is [(C 0 / C 30 )-1] × 100%.
[0100] Tables 1 to 5 show the preparation parameters and performance measurements for each of the Examples and Comparative Examples.
[0101] Table 1. Effect of fluoroethylene carbonate (FEC) content and unit reaction area (c) of the positive electrode active material on cycle performance and storage performance
[0102] [Table 1]
[0103] As can be seen from Examples 1-1 to 1-12 and Comparative Examples 1-1 and 1-2 in Table 1, when the ratio of the content of fluoroethylene carbonate in the positive electrode material to the unit reaction area c of the positive electrode active material is within a certain range, both the battery cycle performance and high-temperature storage performance are improved. This is mainly because fluoroethylene carbonate can be oxidized and decomposed on the positive electrode surface to form a protective layer with the lithium salt in the electrolyte on the positive electrode surface, and based on the unit reaction area of the positive electrode active material, an appropriate content of FEC can protect the positive electrode active material and at the same time reduce the adverse effect of HF generated by the decomposition of FEC on the positive electrode, and at the same time improve the stability of the negative electrode interface during cycle and storage.
[0104] Table 2. Effects of different positive electrode active materials and their particle sizes on cycle performance and low-temperature discharge performance
[0105] [Table 2]
[0106] Table 2 shows the data of Dv10, Dv99, cycle performance and low-temperature discharge performance corresponding to different lithium manganate materials and mixed materials. Here, when the value of a / z is 0.01 to 1, the electrochemical device can maintain excellent overall performance. In particular, when the value of a / z is 0.05 to 0.3, the discharge capacity retention rate of the electrochemical device under low-temperature conditions is significantly improved. This is because, when a / z is maintained within an appropriate range, local side reaction phenomena due to particle size distribution do not occur, and the interface between the positive electrode active material and the electrolyte has overall consistency, which has a relatively positive effect on ion transport performance.
[0107] Table 3. Effect of vinylene carbonate (VC) addition on cycle performance
[0108]
Table 3
[0109] In Table 3, as can be seen from Examples 3-1 to 3-8, the addition of VC can further improve the cycle capacity retention rate and reduce the thickness change during the cycle. In particular, when the contents of VC and FEC satisfy 0.11a - 0.05% < b < 5.1a + 0.45%, the cycle capacity retention rate of the electrochemical device is further improved, and the high-temperature thickness expansion is significantly improved. This is because VC and FEC copolymerize to form a film to form an organic polymerization component. When 0.11a - 0.05% < b < 5.1a + 0.45% is satisfied, the stability of SEI is improved, and the degree of destruction of SEI caused by the elution of Mn 2+ reduction at the negative electrode is reduced, and it is considered that this is to reduce the increase in thickness due to side reactions.
[0110] Table 4 Influence of various additives on storage performance
[0111]
Table 4
[0112] Table 4 shows the influence of the addition of Additive A on storage stability. While improving the generation of gas during high-temperature storage, it can improve the capacity recovery after storage. This is mainly because the combined use of such additives and FEC can reduce the side reactions under the high-temperature storage conditions of the system and reduce the consumption of active lithium by the electrolyte during long-term storage. In particular, when at least one of LiFSI, LiPO 2 F 2 and 2-PY is further added, the comprehensive performance of the electrochemical device is significantly improved.
[0113] Table 5 Influence of the addition of dimethyl carbonate (DMC) on cycle performance and storage performance
[0114]
Table 5
[0115] As can be seen from Examples 5-1 to 5-4 and Examples 1-4 in Table 5, adding a certain amount of DMC can improve cycle performance and storage performance. This is mainly because the presence of a small amount of DMC can suppress the decomposition of EMC and reduce the deterioration of cycle life caused by side reactions, but if the DMC content is too high, the oxidation resistance of DMC becomes insufficient, resulting in gas generation and cycle attenuation during storage.
Claims
1. An electrochemical device comprising a positive electrode, a negative electrode, a separator, and an electrolyte, The electrolytic solution contains fluoroethylene carbonate, and the content a of the fluoroethylene carbonate is 0.01% to 5% based on the mass of the electrolytic solution; the positive electrode includes a positive electrode active material, the positive electrode active material includes a Mn element, and a content of the Mn element is 15% or more with respect to a mass of the positive electrode active material, The unit reaction area of the positive electrode active material is cm 2 / cm 2 wherein a and c satisfy 0.0006≦a / c≦6.25, and the unit reaction area is the product of a weight W of the positive electrode active material per unit area and a specific surface area BET of the positive electrode active material.
2. The electrochemical device comprises: a) a and c satisfy 0.0006≦a / c≦2.5; b) the content of the fluoroethylene carbonate is 0.05% to 5% by mass of the electrolyte; c) W is 8 mg / cm 2 ~35mg / cm 2 The range is 1m 2 / g to 5m 2 / g range. The electrochemical device according to claim 1 , wherein at least one of the following is satisfied:
3. The electrochemical device comprises: a) when Dv10 / Dv99 of the positive electrode active material is z, a / z is 0.01 to 1; b) a and c satisfy 0.001≦a / c≦4.5; The electrochemical device according to claim 1 or 2, which satisfies at least one of the above.
4. The electrolyte further comprises vinylene carbonate, 3. The electrochemical device according to claim 1, wherein the content b of the vinylene carbonate is 0.01% to 5% by mass of the electrolyte.
5. The electrochemical device comprises: a) the b satisfies 0.11a-0.05%<b<5.1a+0.45%; b) In the positive electrode active material, when the content of manganese element is x, b and x satisfy the following relationship: b / x≧10 -3 To satisfy The electrochemical device according to claim 4 , wherein at least one of the following is satisfied:
6. The electrolyte further comprises an additive A, The additive A is at least one selected from the group consisting of methylenemethane disulfonate, 1,3-propene sultone, 1,3-propane sultone, succinic anhydride, lithium difluorophosphate, 2-fluoropyridine, and lithium bis(fluorosulfonyl)imide; 3. The electrochemical device according to claim 1, wherein the content of the additive A is 0.01% to 10% by mass of the electrolyte.
7. The electrolyte further comprises dimethyl carbonate, 3. The electrochemical device according to claim 1, wherein the content of the dimethyl carbonate is 5% or less based on the mass of the electrolyte solution.
8. 3. The electrochemical device of claim 1, wherein the positive electrode active material comprises at least one of lithium manganate and lithium nickel cobalt manganate.
9. The electrochemical device comprises: a) the content of the fluoroethylene carbonate is 0.05% to 3% based on the mass of the electrolyte; b) W is 13 mg / cm 2 ~30mg / cm 2 The range is 1.2m. 2 / g to 3.5m 2 / g range, c) the electrolytic solution further contains vinylene carbonate, and the content of the vinylene carbonate is 0.01% to 2% based on the mass of the electrolytic solution; d) the electrolytic solution further contains dimethyl carbonate, and the content of the dimethyl carbonate is 1% or less based on the mass of the electrolytic solution; e) In the positive electrode active material, the content of Mn element is 60% or less; and f) When Dv10 / Dv99 of the positive electrode active material is z, a / z is 0.05 to 0.
3. The electrochemical device according to claim 1 or 2, which satisfies at least one of the above.
10. An electrical device comprising the electrochemical device according to any one of claims 1 to 9.
Citation Information
Patent Citations
Battery
JP2007012437A
Illumination unit using light guide body, and display device having the same
JP2013206834A
Nonaqueous electrolyte secondary battery
JP2015144104A
Positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2019029205A
Lithium ion secondary battery
WO2014080871A1